Dragons with clay feet?: Transition, sustainable land use, and rural environment in China and Vietnam - Spoor, Max; Heerink, Nico; Qu, Futian (Lexington Books, 2007)
This book presents state-of-the-art research on the impact of ongoing and anticipated economic policy and institutional reforms on agricultural development and sustainable rural resource in two East-Asian transition (and developing) economies--China and Vietnam. The contributions to this volume focus on the regional and sectoral impact of transformational policies, farm household decision making under a changing economic and institutional environment, and potential trade-offs between agricultural growth and sustainable land management in the two countries. The analysis of household responses to economic policies and changing institution, and their implications for agricultural production and sustainable resource use in East-Asian transition economies, is a relatively new research field. This collection by a group of Chinese, Vietnamese, and international researchers reflect the rapid progress that is being made in this important research field.